2021
DOI: 10.1016/j.radonc.2021.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Model based patient pre-selection for intensity-modulated proton therapy (IMPT) using automated treatment planning and machine learning

Abstract: Background and purpose: Patient selection for intensity modulated proton therapy (IMPT), using comparative photon therapy planning, is workload-intensive and time-consuming. Pre-selection aims at avoidance of manual IMPT planning for patients that are in the end ineligible. We investigated the use of machine learning together with automated IMPT treatment planning for pre-selection of head and neck cancer patients, and validated the methodology for the Dutch model based selection (MBS) approach. Materials & me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Liao and colleagues have pointed out the importance of treatment planning experience in PT for NSCLC [11]. In addition to comprehensive treatment planning guidelines, solutions for automated treatment planning could be useful to ensure the high plan quality needed in PBS-PT for LA-NSCLC [38].…”
Section: Discussionmentioning
confidence: 99%
“…Liao and colleagues have pointed out the importance of treatment planning experience in PT for NSCLC [11]. In addition to comprehensive treatment planning guidelines, solutions for automated treatment planning could be useful to ensure the high plan quality needed in PBS-PT for LA-NSCLC [38].…”
Section: Discussionmentioning
confidence: 99%
“…Kouwenberg et al 24 have recently demonstrated how their in-house automatic multicriterial optimizer together with Bayes classification on preselecting patients for plan comparison reduced the number of unnecessary manually planned IMPTs. Although our auto-generated KBPs are intended to offer the user clinically relevant treatment plans with both modalities to aid the planner in about 30 minutes, it would be of interest to see how the auto-generated IMPTs perform in a similar preselection study, as the entire IMPT-portion of the pipeline takes about 10 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Automated planning combined with machine learning approaches can also be used to preselect patients for plan comparison based on delineation [28][29][30][31][32][33][34][35][36][37]. A recent study by Kouwenberg et al investigated the potential of using automated planning in combination with machine learning to be used for preselection in 45 HNC patients who were subjected to model-based selection based on a previous version of the Dutch national indication protocol [37]. They compared the actual photon plan with an IMPT plan that was generated with non-clinical, fully-automated planning.…”
Section: Discussionmentioning
confidence: 99%